Sistem Informasi Geografis Untuk Menentukan Titik Lokasi Cagar Budaya Seribu Rumah Gadang Di Kabupaten Solok Selatan Menggunakan ARCGIS Berbasis Android - Reni Handayani Siregar; Melladia (Riset Sinergi Indonesia (RISINDO), 2025)
The rapid development of information technology has brought significant changes in various aspects of life, including tourism and cultural preservation. One of the cultural heritages located in Solok Selatan Regency is the Seribu Rumah Gadang Cultural Heritage Area, which holds high historical and cultural value. However, limited information regarding the location and description of tourist attractions in this area causes many people and tourists to be unaware of its existence. This research aims to develop a Geographic Information System (GIS) based on Android by utilizing ArcGIS as a platform for mapping the location points of the Seribu Rumah Gadang Cultural Heritage. The system not only displays the location of tourist objects but also provides additional information such as historical descriptions, addresses, and other details to help tourists obtain accurate information. With this application, it is expected to improve information accessibility, support cultural preservation, and contribute to tourism development in Solok Selatan Regency.